An Act Defining Crime and Punishments, 121, Ch. 49, Sec. 20, in Revised Statutes of the Territory of Iowa (Reprint 1911) - (:unkn) unknown (My University, 1843)
Prohibited assault with a deadly weapon, instrument, or other thing with intent to inflict bodily injury. Violators fined not more than one thousand dollars, and imprisoned for a term not exceeding three years.
Keywords: COMMITTING CRIME W/ WEAPON